2021
DOI: 10.1371/journal.pone.0244726
|View full text |Cite
|
Sign up to set email alerts
|

Perceived work environment and patient-centered behavior: A study of selected district hospitals in the central region of Ghana

Abstract: Introduction Quality work environment has been established as a marker of employee value creation. A plethora of qualitative evidence suggested that sustained focus on employee satisfaction through changes in the work environment, communication of patient-centered care strategic vision, management of staff workload, and workplace social support are factors that stimulate Patient-centered care. Yet, it seems that the effect of work environment on the patient-centered behavior of hospital employees has not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Studies have found inadequate health professionals, inappropriate prognoses and therapeutics, inadequate needed capital, poor referral systems, preference of skilled personnel, and previous exposure to complications as health system barriers that affect skilled delivery to mothers (2,5,12,(15)(16)(17). Satisfaction of patients with skilled delivery has been reported to be associated with sociodemographic factors (Figure 1) (1, 4, 7-9, 14, 18, 19), long waiting time (4,14,19), treatment outcome (2,(18)(19)(20), availability, and preference of healthcare providers (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found inadequate health professionals, inappropriate prognoses and therapeutics, inadequate needed capital, poor referral systems, preference of skilled personnel, and previous exposure to complications as health system barriers that affect skilled delivery to mothers (2,5,12,(15)(16)(17). Satisfaction of patients with skilled delivery has been reported to be associated with sociodemographic factors (Figure 1) (1, 4, 7-9, 14, 18, 19), long waiting time (4,14,19), treatment outcome (2,(18)(19)(20), availability, and preference of healthcare providers (2,4).…”
Section: Introductionmentioning
confidence: 99%
“…After duplicates and conference reports were removed, 24 papers remained, and based on the team members’ intensive reading, 8 papers were considered for inclusion. The retrieved articles ( 5 , 12–15 , 24–26 ) were assessed independently by two authors, information was extracted from the eligible studies, and the English items were preliminarily translated.…”
Section: Methodsmentioning
confidence: 99%
“…Early studies of environmental psychology mostly focused on the impact of the physical environment on people’s mental health and behavior, including factors such as noise, air pollution, climate, and related architectural design ( 1–3 ). With the change in social problems, environmental psychology focuses more on exploring the relationship between social environment factors and human behavior ( 4 , 5 ). Hence, in the study, the organizational environment comprised the psychological and social environment perceived by employees.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, perceived relationship with colleagues refers to the peer relation of co-workers that are in the same or similar position level in the organization, represented by friendliness and kindness from colleagues. Studies have found that co-worker support is considered to be predictors of the employees' behavior [47]. However, such influences may differ with different genders, and studies have proved that perceived co-worker support was more strongly related to organization commitment which is typical outcome of job satisfaction for women than for men [48].…”
Section: Interpersonal Relationshipmentioning
confidence: 99%